Controlling the carbon-bio interface via glycan functional adlayers for applications in microbial fuel cell bioanodes - Scanlan, Eoin; Colavita, Paula (My University, 2021)
Surface modification of electrodes with glycans was investigated as a strategy for modulating the development of electrocatalytic biofilms for microbial fuel cell applications. Covalent attachment of phenyl-mannoside and phenyl-lactoside adlayers on graphite rod electrodes was achieved via electrochemically assisted grafting of aryldiazonium cations from solution. To test the effects of the specific bio-functionalities, modified and unmodified graphite rods were used as anodes in two-chamber microbial fuel cell devices. Devices were set up with wastewater as inoculum and acetate as nutrient and their performance, in terms of output potential (open circuit and 1 kΩ load) and peak power output, was monitored over two months. The presence of glycans was found to lead to significant differences in startup times and peak power outputs. Lactosides were found to inhibit the development of biofilms when compared to bare graphite. Mannosides were found, instead, to promote exoelectrogenic biofilm adhesion and anode colonization, a finding that is supported by quartz crystal microbalance experiments in inoculum media. These differences were observed despite both adlayers possessing thickness in the nm range and similar hydrophilic character. This suggests that specific glycan-mediated bioaffinity interactions can be leveraged to direct the development of biotic electrocatalysts in bioelectrochemical systems and microbial fuel cell devices.
PUBLISHED
cited By 0
Keywords: aryldiazonium; functionalization; carbon; microbial fuel cells; bioanodes; electrocatalysis; bioelectrochemical systems